Antioxidant effects of curcumin in models of neurodegeneration, aging, oxidative and nitrosative stress: A review. (15th May 2019) - Abrahams, Shameemah; Haylett, William L.; Johnson, Glynis; Carr, Jonathan A.; Bardien, Soraya
Abstract: The global burden of neurodegenerative disorders has increased substantially over the past 2 decades due to rising rates of population aging. Although neurodegenerative disorders differ in their clinical presentation, the underlying pathobiological processes are largely shared. Oxidative stress, among other mechanisms, is strongly implicated in neurodegenerative disorders and aging, and can potentially be targeted by antioxidative agents. Curcumin, a component of turmeric, is a compound that has received considerable attention for its therapeutic properties, and it is considered to be a powerful antioxidant. In this review, we analyzed the evidence for curcumin as an antioxidant in models of neurodegenerative disorders as well as oxido-nitrosative stress. A total of 1451 articles were found from 3 scientific literature databases (PubMed, Scopus, and Web of Science). After all exclusions, a final total of 64 articles were included in this review. The majority of the studies showed that curcumin, or derivatives thereof, were protective against oxidative and/or nitrosative stress in various cellular and animal models. Overall, curcumin protected against lipid and protein oxidation with a reduction in levels of malondialdehyde, and protein carbonyls, thiols and nitrotyrosines. Furthermore, it stimulated the activities of antioxidant enzymes such as superoxide dismutase and glutathione peroxidase. In conclusion, curcumin appears to be a promising compound for phytomedicine. However, due to some concerns about its efficacy, further targeted experiments are needed to identify its exact molecular targets and pathways responsible for its antioxidant effects. Highlights: 64 relevant articles were found in animal and cellular models of neurodegeneration, aging and oxido-nitrosative stress. The majority of studies showed curcumin alleviated oxidative stress under a wide range of experimental conditions. Curcumin inhibited lipid and protein oxidation by suppressing malondialdehyde and protein carbonyls. Curcumin stimulated the activities of various antioxidant enzymes, including superoxide dismutase and catalase.